Term as an essential element of English aviation lexis (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article gives the analyses of the notion of «term», its characteristic features. The views of the researchers on division of aviation terminology into lexico-semantic groups are studied and a brief characteristic of the peculiarities of usage of lexical units during professional communication between pilots and air traffic controllers in particular is given.
Keywords: term aviation English vocabulary; a field approach; lexical-semantic groups